KETERSEDIAAN NITROGEN PADA TIGA JENIS TANAH AKIBAT PEMBERIAN TIGA BAHAN ORGANIK DAN SERAPANNYA PADA TANAMAN JAGUNG - Intan Nariratih; Muhammad Majid B Damanik; Gantar Sitanggang Gantar Sitanggang (Universitas Sumatera Utara, 2013)
This research concernsof knowing nitrogen(N) availability in soil, N-plant absorption andplant growth in three different kinds of soil with the incrementof three organic matters fromdifferent sources. The research conducted at the screen house, Chemistry and Fertility Laboratory,and Research and Technology Laboratory, Faculty of Agriculture, University of North Sumatera,Medan. This researchused Randomized Block Designed (RBD) Factorial that consists of twofactors and three repeatations which had made thirty six units of experiment. The first factor are thekind of soil (T) that consists of Entisol soil (T1), Inceptisol soil (T2) and Ultisol soil (T3), and thesecond factor are the organic matter (K) that consist of rice straw compost (K1), chicken dirt (K2),cocoa shell compost (K3), and control (K0). The resultof the research showed that different kind ofsoil singnificanly influencedthe C-organic soil, and total soil N, and the difference of organic mattersingnificanly influenced the total soil N, plant crowndry weight, N-absorptionof the plant and plantgrowth, and the interaction between each different kind of soil with different organic mattersingnificanly influenced the plant crowndry weight.